Evaluation of sexual dysfunction and its associated factors in primary open angle glaucoma patients - Chee, Chew Chia (2021)
INTRODUCTION Malaysia is expected to be an aging nation by 2030. Sexual dysfunction (SD) and primary open angle glaucoma (POAG) are diseases that generally affect older population. The prevalence of both diseases is increase with age. Moreover, human life expectancy increases over time. POAG is the most common form of glaucoma and is known as 'silent thief of sight'. SD affects quality of life on top with the treatment burden from POAG. Thus, consideration to confront the older adults is important to warrant an individual's future well-being. OBJECTIVE The aim of this study is to evaluate sexual dysfunction (SD) and its associated factors in primary open angle glaucoma patients. METHODOLOGY A cross sectional study was conducted from September 2019 to September 2020 involving three ophthalmology clinics in Malaysia: Hospital Raja Permaisuri Bainun (HRPB), Hospital Raja Perempuan Zainnab II (HRPZ II) dan Hospital Universiti Sains Malaysia. Only participants aged between 40-80 years old who attended clinic and able to provide two consecutive reliable and reproducible Humphrey visual fields (HVF) 24- 2 were recruited. Participants were interviewed on demographic data and latest health status. Severity of glaucoma was based on modified Advanced Glaucoma Intervention Study (AGIS) scoring system on HVF and categorized into mild, moderate and severe glaucoma. SD assessment was done using validated Bahasa Malaysia version of 'International Index of Sexual Function' (IIEF-5) for male POAG participants and 'Female Sexual Function Index' (FSFI-6) for female POAG participants. RESULT A total of 432 participants with pre-existing POAG were recruited (222 men and 210 women). Men and women were assessed and analyzed differently by using two different questionnaires. Prevalence for erectile dysfunction (ED) was 91% by using IIEF-5 questionnaire and prevalence rate of female sexual dysfunction (FSD) was 78.5% by using FSFI-6 questionnaire. Prevalence of ED and FSD increased with age. There was significant association between ED and severity of glaucoma (p<0.001) but not found in FSD. High educational level had 67% lower odds to experience FSD compared to lower educational level (OR=0.33, 95% CI=0.12, 0.88). For 1 year older in male POAG patients, there were 1.23 times odds to experience ED (OR=1.23, 95% CI=1.10, 1.38). CONCLUSION Prevalence of SD is high in patients with POAG in our study population. Malaysia is expected to be aging nation by 2030. Sexual health in older adults should not be overlooked as both diseases are affecting them. Sexual health is an integral part of overall health in older life and quality of life includes the pleasure of sexual activity.